Fear of Missing Out (FOMO) and Scarcity Strategies: A Qualitative Exploration of Consumer Communication with Flash Sales on E-Commerce Platforms - Fitria Mayasari; Nurrahmi; Salsabila, Fahmi (Jogjakarta Communication Conference (JCC), 2025)
This research investigates the impact of the psychological concept of Fear of Missing Out (FOMO) and scarceness marketing strategies on consumer interactions and behaviors during ecommerce flash sales. A qualitative approach was selected to delve into emotions, experiences, and cognitive aspects of decision-making through in-depth interviews with active online shoppers. Results show that FOMO is linked to an increase in feelings of volatility and escalation, which encourages greater and more rapid emotion-laden purchasing behavior that is not thoroughly reasoned out. Countdown clocks and limits on available stock are scarcity strategies that increase the intensity of value placed on the items which make them more desirable and exclusive. Furthermore, the study revolves around consumers’ perception of flash sales—extensively shared on social media and other peer networks—illustrating that their personal and social narratives often fuel a collective feeling of urgency. This underscores powerful intersectional dynamics of modern corporate marketing strategies and consumer behavior vis-a-vis the approaches that need to be adopted, especially from an ethical standpoint, in e-commerce business systems.